Recapturing the timeless past in selected science-based postmodern British plays through lens of chaos theory - Yas, Khalid Ahmad (2018)
Recapturing the past is a marked feature of postmodern science plays. McBurney, Wertenbaker, and Stephenson established themselves vigorously in historical representations to trace both the root and the fruit of a scientific phenomenon. Unlike traditional plays; where the events are chronologically and spatially fitted into a linear causal process, contemporary science dramas created by the dynamic interaction of all theatrical elements and governed by an internal logic simulate the structure and behaviour of a chaotic system. Due to this similarity, the study utilises the key-facets of chaos theory, i.e., The Butterfly Effect, Strange Attractors and Recursive Symmetries, as a theoretical and methodological framework to investigate how timeless past can secure a better understanding of the fragmented reality, and how the science of chaos and the selected science plays are interrelated in providing answers to the main characters’ most pressing questions about the origin, purpose, and end of life. It also endeavours to examine how chaos key-facets can help in identifying the inciting events that trigger conflict, recognizing thematic concepts that control and guide the behaviour of the characters, and exposing order amid fragmentation and formlessness of the selected texts, which in turn can elucidate the significance of a cross-discipline approach, chaos theory, in reading the chosen science dramas. While Mnemonic and A Disappearing Number appropriated the physiological process of remembering and mathematical patterns to tackle concepts like identity and eternity, After Darwin and An Experiment with an Air Pump employed biological and social Darwinism, cadavers and genetics to address issues related to the post-Darwinian world and the danger of extending the natural selection to society. The double frame of a story from the past interwoven with another one from the present is used deliberately to allow each period to comment on the other. However, at the end of each drama, time and place disappeared, the personal turned into collective, and the fragmented, intertwined stories are combined to present a universal image. While Alice of Mnemonic abandons her personal quest for identity to embrace a bigger one, the whole humanity, Al of A Disappearing Number realises that a full union with a beloved is possible, but only in the world of infinity. Lawrence of After Darwin presents adaptation as a solution to survive the post- Darwinian world. Instead of resisting evolution, one has to be adaptable. Endowed with brains work independently, humankind is the only species qualified enough to turn the table against the brutality of natural selection and establish its own values. Whether to understand or change the world, Fenwick and Ellen of An Experiment with an Air Pump state openly that science is not entirely morally-free, and heart should come first sometimes. Instead of being a tool of liberation, science in a market-driven culture could be turned into a weapon of oppression and discrimination. By interweaving past with the present, the playwrights reveal not only the level of determinism, but also how chaos works in the universe. It occurs when human desires disrupt the natural sequence of order and spark a chain reaction. Such an act operates like the butterfly effect, where reversing the process or predicting the consequences becomes so difficult. Briefly, the achievement made by the selected dramas lies not only in presenting hard science in an accessible way or challenging the old axiom that art and science cannot coexist, but also in merging universal humanism with contemporary science to reveal that Man is not only affected by the chaotic inclination of the world, but he is also a fundamental part of it. He can create as much disorder as order and can affect change within a system through his own choice. The study can be further developed to cover some more aspects. A survey study can be conducted to trace the evolution of science play from Dr. Faustus until the present time as the current research focuses on the last stage of this development. The study also can be taken as a springboard to compare between American and British science dramas. Due to its rich language and method, chaos theory can also be extended to include classical literature; Shakespearean tragedies are one possible area.